A connection between γ-ray and parsec-scale radio flares in the blazar 3C 273 - Lisakov MM; Kovalev YY; Savolainen T; Hovatta T; Kutkin AM (OXFORD UNIV PRESS, 2022)
We present a comprehensive 5-43 GHz VLBA study of the blazar 3C 273 initiated after an onset of a strong gamma-ray flare in this source. We have analysed the kinematics of newborn components, light curves and position of the apparent core to pinpoint the location of the gamma-ray emission. Estimated location of the gamma-ray emission zone is close to the jet apex, 2-7 pc upstream from the observed 7 mm core. This is supported by ejection of a new component. The apparent core position was found to be inversely proportional to frequency. The brightness temperature in the 7 mm core reached values up to at least 1013 K during the flare. This supports the dominance of particle energy density over that of magnetic field in the 7 mm core. Particle density increased during the radio flare at the apparent jet base, affecting synchrotron opacity. This manifested itself as an apparent core shuttle along the jet during the 7 mm flare. It is also shown that a region where optical depth decreases from tau similar to 1 to tau << 1 spans over several parsecs along the jet. The jet bulk flow speed estimated at the level of 12c on the basis of time lags between 7 mm light curves of stationary jet features is 1.5 times higher than that derived from very long baseline interferometry apparent kinematics analysis.